Start-up improvement of a supplementary-fired large combined-cycle power plant. (April 2018) - Alobaid, Falah
Highlights: Dynamic simulation model of 350 MWth supplementary-fired combined-cycle power is developed. All process, automation and electrical components of the real power plant are modelled. Dynamic simulations of switching off the supplementary firing, part loads and start-ups are carried out. GT start-up time reductions by 30%, 80% and 93% in hot, warm and cold start-ups is achieved. HRSG reaches faster its nominal power output by 38%, 31% and 20% in hot, warm and cold start-ups. Abstract: The start-up time of a combined-cycle power plant depends mainly on the heat recovery steam generator (HRSG) with its thick-walled tubes. This work contributes to a start-up time reduction of a large combined-cycle power plant (CCPP) with a supplementary-fired HRSG. Hence, a dynamic simulation model is developed using the advanced process simulation software (APROS). The flue gas path and the water/steam side are modelled in detail. All control structures required for the plant operation are implemented, e.g. drum, steam turbine bypass system and steam temperature control. The comparison between model predictions and design data at different load changes shows high correlation towards given data with an average relative error of 5%. Using the developed model, hot, warm and cold start-ups are simulated and finally three different reduced start-up times of gas turbine (15 min, 24 min and 38 min) are evaluated. A comparison between baseline and improved start-ups reveals time saving and fast power generation rate.